Investigating the Role of Periphyton in Nitrification in Paddy Fields - H.R. Zare Guildehi; H.A. Alikhani; H. Etesami; M. Shirinzadeh; Z. Karami; M. Gholami (علوم آب و خاک)
Soil and water pollution and waste of resources have occurred due to the excessive use of nitrogen fertilizers in paddy fields. Considering that the biofilm of periphyton formed in paddy fields is mainly responsible for the exchange of nutrients, the present research was designed to investigate the effect of periphyton in the nitrification process in paddy fields and performed with 12 treatments. The treatments included powerful and weak nitrifiers isolated from periphyton, periphyton, periphyton enriched with nitrifiers, and their combination with a dicyandiamide chemical inhibitor. The research was carried out in a rice greenhouse cultivation for 30 days. The results showed that the simultaneous application of periphyton enriched with low-power nitrifier and dicyandiamide can increase the amount of total soil nitrogen, soil phosphorus, soil ammonium, total plant nitrogen, plant phosphorus, plant potassium, shoot length, and dry weight of rice plants. While this treatment reduced the conversion of ammonium to nitrate and subsequently reduced the potential of nitrate formation in the soil, with the increase of ammonium accumulation, it increased the utilization of rice plants. Periphyton can be considered a source for the isolation of nitrifiers. Also, the use of periphyton in paddy fields as a biological and healthy solution to inhibit the nitrification process in front of the use of inhibiting chemicals is placed in the path of future research.